2004
DOI: 10.1002/sia.1601
|View full text |Cite
|
Sign up to set email alerts
|

Surface segregation of silicon impurities in organic materials

Abstract: The present revolution in novel organic materials is driven by the synthesis of new materials exhibiting specific functional properties. Traces of silicon compounds are often present in these materials and, although the bulk concentrations of these impurities may be low, segregation can seriously modify the surface composition. Surfaces and interfaces play an important role in many applications, and the intrinsic properties of the materials are thus often obscured by the presence of segregated impurities.By st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Siloxanes are a common trace impurity with organic compounds, usually at low enough bulk levels to be insignificant for bulk properties. However, they have a low solubility in the crystal bulk and therefore have a tendency to accumulate at the surface, resulting in a significant contribution to the photoemission . The presence of siloxanes would increase the carbon and oxygen content, just as seen in the data (Table ), particularly an enhanced C − C component at 285 eV.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Siloxanes are a common trace impurity with organic compounds, usually at low enough bulk levels to be insignificant for bulk properties. However, they have a low solubility in the crystal bulk and therefore have a tendency to accumulate at the surface, resulting in a significant contribution to the photoemission . The presence of siloxanes would increase the carbon and oxygen content, just as seen in the data (Table ), particularly an enhanced C − C component at 285 eV.…”
Section: Resultsmentioning
confidence: 92%
“…Both RGD and RGDSC exhibit a Si signal in XPS, signifying a further impurity. The BE of the Si 2p signal around 102 eV is indicative of Si − O species, such as those found in siloxanes, Si(−R)O, where R is a hydrocarbon chain . Siloxanes are a common trace impurity with organic compounds, usually at low enough bulk levels to be insignificant for bulk properties.…”
Section: Resultsmentioning
confidence: 99%
“…λ N 1s in BN and λ B 1s in BN are inelastic mean free paths (IMFP) of the photoelectrons in the BN film with kinetic energies that correspond to the N and B core levels, respectively. The IMFP values were obtained from a recent report by Tanuma et al 39 IMFP values of graphite are available in the report, but, while those of BN are not available. We assumed the same IMFP for both graphite and BN for the following reason.…”
Section: A Film Composition and Thicknessmentioning
confidence: 99%
“…I Ni 3s is the intensity of the photoelectron peak of the Ni 3s level, which was obtained from Fig. 1 39,42 Due to the difference of the IMFP values between the two methods, the thickness of the BN film was estimated to be 6.6 Å by the new IMFP values and 7.5 Å by the IMFP values from the TPP-2M equation. For further discussion, we suppose that the thickness of the film as 6.6 Å.…”
Section: A Film Composition and Thicknessmentioning
confidence: 99%
“…Gorelova et al [12] reported that the surface segregation of a dilute blend of PDMS with polychloroprene (PCP) decreased substantially with increasing molecular weight of the siloxane. Reijme et al [13] also noted that traces of silicon-based impurities in organic materials can also segregate to the surface and may seriously modify the surface composition, sometimes adversely.…”
Section: Introductionmentioning
confidence: 97%